Reexamination In Vitro and In Situ of an Antibacterially Modified Experimental Dental Resin Composite with Molecular Methods: A Pilot Study - Birgit Henrich; Ilka Hermann; Mara Di Giulio; Karl Köhrer; René Deenen; Sugi Sivalingam; Ulrike Peters; Thomas Beikler; Ralf Janda; Stefan Rüttermann (Advances in Materials Science and Engineering)
Purpose. To introduce additional methods to detect and to quantify single pathogens in the complex biofilm formation on an antibacterial dental material. Materials and Methods. A conventional (ST) and an antibacterial dental composite (B) were manufactured. In vitro: specimens were incubated with a mixture of early colonizers. Bacterial adhesion was analyzed by TaqMan PCR after 8/24 h. In situ: TaqMan PCR and 16S rRNA Next Generation Sequencing (NGS) were performed. Results. In vitro: after 8 h incubation, B was covered by 58.6% of the bacterial amount that was attached to ST. After 24 h, the amount of attached bacteria to ST remained constant on ST only slightly lower on B. In situ: after 8 h the amount of adhering A. viscosus and S. mitis was prominent on ST and reduced on B. NGS revealed that S. sanguinis, S. parasanguinis, and Gemella sanguinis were the mainly attached species with S. sanguinis dominant on ST and S. parasanguinis and G. sanguinis dominant on B. Conclusions. Initial biofilm formation was altered by B. A shift between actinomycetes and streptococci was observed in situ. TaqMan PCR and 16S rRNA NGS revealed comparable results in situ and demonstrated the usefulness of NGS to characterize complex bacterial communities.